EPD of Finnish sawn and planed timber - Räty, Tarmo; Jallinoja, Marja (The Building Information Foundation RTS sr, 2021)
This environmental product declaration (EPD) is for sawn and planed softwood timber produced by member companies of the Finnish Sawmills Association. The declaration has been prepared in accordance with standard EN 15804:2019 + A2 and RTS PCR (version 1.6.2020) product category rules. The environmental data for building products mentioned in this RTS EPD cannot be compared to other EPDs if they do not meet the requirements set out in SFS-EN 15804:2019, 5.3
Keywords: sawn timber; planed timber